212k views
4 votes
((x-j) ÷ k) + m =n what does x equal?

1 Answer

4 votes

x=nk-mk+j

Step-by-step explanation


(x-j)/(k)+m=n

Step 1

subtract m in both sides


\begin{gathered} (x-j)/(k)+m=n \\ (x-j)/(k)+m-m=n-m \\ (x-j)/(k)=n-m \end{gathered}

Step 2

multiply each side by k


\begin{gathered} (x-j)/(k)=n-m \\ (x-j)/(k)\cdot k=(n-m)\cdot k \\ x-j=(n-m)\cdot k \end{gathered}

Step 3

finally, add j in both sides


\begin{gathered} x-j=(n-m)\cdot k \\ x-j=nk-mk \\ x-j+j=nk-mk+j \\ x=nk-mk+j \end{gathered}

I hope this helps you

User Raynita
by
4.7k points